Mini Karnival KPT Prihatin Keluarga Malaysia assists Mersing residents - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
Mersing, 5 March 2022 - The Mini Karnival KPT Prihatin Keluarga Malaysia Programme, which took place at the Futsal Rink of Kampung Nelayan and Tenglu Laut Open Hall, Mersing recently benefited the local community by giving them the opportunity to get health checks, free motorcycle service and information on admission to Higher Education Institutions (HEI), especially for high school students.